Modelo de evaluación para procesos de formación posgradual en ciencias administrativas (2020)
Postgraduate training pose a challenge for students, professors and institutions since multiple expectations must be met for a diverse student population and at high levels of quality demanded by the inspection and control bodies of educational processes, as well as those whocoordinate, plan, recommend and advise on processesof high quality accreditation of programs and institutionsof higher education. In this sense, it is necessaryto have evaluation models for dynamic training processes,which enhance interaction between the players inthe teaching-learning process while entails a source ofopportunities for improving the quality of training andthe achievement of learning results in training coursesor spaces and in the academic program. Therefore, thismethodological propose a model for the evaluation ofpostgraduate training processes in administrative sciences,which is composed of 5 dimensions (Diagnose,motivate, transmit, contextualize and apply) accordingto their intentionality and includes a feedback centralelement useful to make the required didactic and pedagogicaladjustments in any of the stages.